Asymmetric Warfare Through the Communication of Threats - Mendelek, Miguel (2020)
For more than thirteen years now, Hezbollah and Israel, against all the odds of asymmetric deterrence, have been maintaining a relatively stable deterrence status quo. After the deployment of Katyusha rockets in 1992, and starting in 1996, Hezbollah established with Israel a set of rules, commonly known as, the “rules of the game”, to mediate their military confrontation on the lines of deterrence. Importantly, throughout the evolution of the deterrence relationship between both parties, Sheikh Hassan Nasrallah’s discourse and speeches have become a centerpiece to assess Hezbollah’s military capability, its will, and its commitment to deter Israel. After Israel’s withdrawal from Lebanon in 2000, and specifically during the 2006 war, Nasrallah, as the Secretary General of Hezbollah, further bolstered the party’s discourse of deterrence vis a vis Israel. In this context, this research work builds primarily on the analysis of Nasrallah’s speeches and statements that focus on deterrence, as translated exclusively in this thesis from Arabic to English, starting in 1992. This thesis evaluates an understudied case, asymmetric deterrence in the Middle East, by testing the theory of deterrence on Hezbollah and Israel. Likewise, it analyzes the translatability, thus, the efficacy of Hezbollah’s exponential growth in military capability, as reflected in Nasrallah’s and the party’s discourse of deterrence between the years 1992 and 2019.